Paroxysmal nocturnal hemoglobinuria presenting as acute renal injury - Saini, Sandeep; Koley, Himadri; Dhoot, Dipesh K.; Cheluvaiah, Chandrashekar; Puri, Rohit; Karunanidhi, Devada S.; Jatteppanavar, Basavaraj; Biswal, Anshuman; Ahlawat, Parul (International Journal of Research in Medical Sciences, 2024)
Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired chronic hemolytic anemia characterized by persistent intravascular hemolysiswith occasional or frequent recurrent exacerbations. In addition to hemolysis, there may be, pancytopenia and a distinct tendency to venous thrombosis. This triad makes PNH a truly unique clinical condition; however, not all of these three features manifest on presentation. Not many reports of renal involvement in PNH are available in the literature. We report a case of acute kidney injury (AKI) due to PNH. This case shows AKI as one of the complications of PNH.